CHAT FOR TELEVISION NETWORK - BOUILLOUX-LAFONT, Hélène; AGLAN, Issam; TESSIER, Emmanuel; LEMAITRE, Hervé (2017)
A chat system for a digital television network comprises a digital operator head end system (301) for broadcasting to subscriber decoders (309). The head end system comprises a chat room creation device (307) which communicates with a chat server (314) to create, cancel and/or join an event related chat room, a timer device (306) which may be programmed to activate itself at the occurrence of an event and automatically sends a request for creation of a chat room to the chat room creation device, a broadcast device (310, 311, 313) used for preparing a transmission of information to the subscriber decoders, and a notification server (308) to generate a notification message to be transmitted by the broadcast device, the notification message being related to the creation of an event related chat room.